Scaling-up Embung Tadah Hujan Untuk Irigasi Pertanian - Sudianto, Sudianto; Dyah Kurniawati, Ajeng; Ni’amah, Khoirun (TEKIBA : Jurnal Teknologi dan Pengabdian Masyarakat, 2024)
Kedungbenda Village, Purbalingga, faces agricultural irrigation problems due to dependence on erratic rainfall, especially during the dry season, exacerbated by the El Niño phenomenon. Rain-fed reservoirs are proposed as a solution to increase the availability of irrigation water. Through the rain-fed reservoir scaling-up program, the water storage capacity is significantly increased. As a result, the planting frequency, which was previously only one to two times per year, increased to three times per year, contributing to increased agricultural productivity. The total area of ​​irrigated land also increased, from three to five rice fields per reservoir to a larger area with eight active reservoirs. In addition, the impact of drought was successfully minimized so that farmers could still manage their land even during the long dry season. This program also increased farmers' awareness of the importance of sustainable water management through water management training. However, challenges still exist in terms of reservoir maintenance, especially related to sedimentation. In the future, a more intensive maintenance strategy is needed to maintain the sustainability of the reservoirs.